2016
DOI: 10.1038/nature19341
|View full text |Cite
|
Sign up to set email alerts
|

Potassium isotopic evidence for a high-energy giant impact origin of the Moon

Abstract: The Earth-Moon system has unique chemical and isotopic signatures compared with other planetary bodies; any successful model for the origin of this system therefore has to satisfy these chemical and isotopic constraints. The Moon is substantially depleted in volatile elements such as potassium compared with the Earth and the bulk solar composition, and it has long been thought to be the result of a catastrophic Moon-forming giant impact event. Volatile-element-depleted bodies such as the Moon were expected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
140
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(157 citation statements)
references
References 29 publications
17
140
0
Order By: Relevance
“…Equilibration between moonlets and the vapor of the synestia would produce an isotopically heavy Moon compared to Earth, but since the equilibration occurs at relatively high pressures and temperatures, the degree of fractionation is expected to be small. Recently, a potassium isotope fractionation has been measured between lunar and terrestrial samples that is consistent with condensation at high pressures and temperatures (Wang & Jacobsen, ). Further development of our model could make predictions as to the degree of fractionation of other elements.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Equilibration between moonlets and the vapor of the synestia would produce an isotopically heavy Moon compared to Earth, but since the equilibration occurs at relatively high pressures and temperatures, the degree of fractionation is expected to be small. Recently, a potassium isotope fractionation has been measured between lunar and terrestrial samples that is consistent with condensation at high pressures and temperatures (Wang & Jacobsen, ). Further development of our model could make predictions as to the degree of fractionation of other elements.…”
Section: Discussionmentioning
confidence: 89%
“…They also suggested that the lunar volatile element depletion could be explained if the material that formed the observable Moon was a partial condensate of disk material. Wang and Jacobsen () recently reported that the potassium isotopes of the Moon are heavier than BSE, which supports the idea of partial condensation. However, the model presented by Canup et al () does not quantitatively explain the magnitude, nor pattern, of moderately volatile element depletion observed for the Moon.…”
Section: Introductionmentioning
confidence: 87%
“…The bulk U and Th abundances of the present day are taken as 25.7 and 102.8 ppb (Th/U = 4), respectively (e.g., Taylor, 1982). The Moon is highly depleted of the volatile element K (Albarede et al, 2014;Jones & Palme, 2000;Wang & Jacobsen, 2016). We neglect the K contribution to the thermal budget in most of our calculations.…”
Section: Physical and Chemical Properties Of The Ibc Layermentioning
confidence: 99%
“…The proportion of KREEP-bearing cumulates, flowing with the IBC, is also determined by the overturn process. The Moon is highly depleted in the volatile element K [Wang and Jacobsen, 2016;Albarede et al, 2014;Jones and Palme, 2000]. The bulk U and Th abundances are used to estimate the heat generation rate in KREEP.…”
Section: Model Formulationmentioning
confidence: 99%
“…The bulk U and Th contents at the present-day are taken to 25.7 ppb and 102.8 ppb (Th/U = 4) [e.g., Taylor, 1982]. The Moon is highly depleted in the volatile element K [Wang and Jacobsen, 2016;Albarede et al, 2014;Jones and Palme, 2000]. Our test model shows that K content (based on K/U ratio of 2500 [Taylor, 1982]) does not affect the instability of IBC-rich layer ( Table S1 in the supporting information).…”
Section: Model Formulationmentioning
confidence: 99%